Reversible induction of mitophagy by an optogenetic bimodular system - Pasquale D’Acunzo (Nature Portfolio, 2019)
Autophagic degradation of mitochondria (mitophagy) is a key quality control mechanism in cellular homeostasis, and its misregulation is involved in neurodegenerative diseases. Here the authors develop an optogenetic system for reversible induction of mitophagy and validate its use in cell culture and zebrafish embryos.